Under siege : P.L.O. decisionmaking during the 1982 war - Khalidi, Rashid (New York : Columbia University Press, 1986)
A fascinating and often terrifying firsthand account of the 1982 war in Lebanon, Under Siege vividly reveals the complex negotiations and military maneuvers which ended with the evacuation of the P.L.O. from Beirut. Rashid Khalidi, a Palestinian, lived with his family in Beirut during the siege and ensuing massacres. Using many usually inaccessible sources, such as P.L.O. telexes and government messages, and interviews with key military officials and diplomats, he tells the story from the compelling viewpoint of those living amid the fighting. Khalidi provides a carefully detailed picture.
Table of Contents; Preface to the 2014 Reissue; Preface; Introduction; 1. The P.L.O. and the Lebanese Before the 1982 War; 2. The Fall of South Lebanon and the Siege of Beirut: A Military Overview; 3. P.L.O. Decisions: The Military Inputs; 4. June 1982: The Decision to Leave Beirut; 5. July 1982: The Decision to Accept the Habib Plan; 6. Wartime Decisions and Their Consequences; Appendix; List of Abbreviations; Cast of Characters; Notes; Bibliography; Supplementary Bibliography; Index.
Includes bibliographical references (pages 215-233) and index.
Print version record.
JSTOR
Keywords: Munaẓẓamat al-Taḥrīr al-Filasṭīnīyah.; Munaẓẓamat at-Taḥrīr al-Filasṭīniyyah.; Munaẓẓamat al-Taḥrīr al-Filasṭīnīyah; Lebanon -- History -- Israeli intervention, 1982-1985.; Palestinian Arabs -- Lebanon -- Politics and government; Palestiniens -- Liban -- Politique et gouvernement; Liban -- Histoire -- 1982-1985 (Invasion israélienne); HISTORY -- Middle East -- General; HISTORY -- Middle East -- Israel; Palestinian Arabs -- Politics and government; Lebanon; 1982-1985; History